Friday

March 6, 2015

March 6, 2015

Posted by **Anna** on Tuesday, July 24, 2012 at 2:40pm.

(3x^2-2x-13)divided by (x-2)

- Algebra -
**Henry**, Wednesday, July 25, 2012 at 9:24pm(3x^2 - 2x - 13) / (x-2) = (3x + 4),

-5 Remainder.

Long division was used, but it is difficult to show here.

Check:

(x-2)(3x+4) =

3x^2 + 4x -6x - 8 =

(3x^2 - 2x -8) -5 = 3x^2 - 2x - 13.

**Answer this Question**

**Related Questions**

Algebra - 1. 2 divide by 2/3+ 3 divide by 4 divide by 4/5= 2. If 2/5 of 2/3 ...

math evluating expressions - I have problems that I need help with can someone ...

algebra 1 - divide and simplify . 1. 5x^4/3 divided by 5x^2/6 2. 3/a^5 divided ...

Math - Divide. Write in simplest form. 5. 1/3 divided by 2/5=5/6 6. 1/9 divided ...

Algebra - Divide using long division: 6x3 + 19x2 + x – 10 divided by 2x -1 ...

Algebra - 1. LCM of 15x^7 and 45x^7 2. Marla can shovel the driveway in 60min ...

Estimation decimal quotient - Use compatible numbers to find the each quotient...

Math - Divide write in simplest form 13. 3/4 divided by 7/12=1 3/28 14. 9/10 ...

algebra 1 help please ASAP - Divide and simplify. 1. 2y^2 - 7y + 3/2y^2 + 3y - 2...

Math - Please check my work. 1) 64 divide -4 = -16 2) -144 divide (-9) = 16 3) ...